Early Illness Features Associated With Mortality in the Juvenile Idiopathic Inflammatory Myopathies1. Issue 5 (May 2014) - Huber, Adam M.; Mamyrova, Gulnara; Lachenbruch, Peter A.; Lee, Julia A.; Katz, James D.; Targoff, Ira N.; Miller, Frederick W.; Rider, Lisa G.; ,
<x xml:space="preserve">Abstract</x> Objective Because juvenile idiopathic inflammatory myopathies (IIMs) are potentially life‐threatening systemic autoimmune diseases, we examined risk factors for juvenile IIM mortality. Methods Mortality status was available for 405 patients (329 with juvenile dermatomyositis [DM], 30 with juvenile polymyositis [PM], and 46 with juvenile connective tissue disease–associated myositis [CTM]) enrolled in nationwide protocols. Standardized mortality ratios (SMRs) were calculated using US population statistics. Cox regression analysis was used to assess univariable associations with mortality, and random survival forest (RSF) classification and Cox regression analysis were used for multivariable associations. Results Of 17 deaths (4.2% overall mortality), 8 (2.4%) were in juvenile DM patients. Death was related to the pulmonary system (primarily interstitial lung disease [ILD]) in 7 patients, gastrointestinal system in 3, and multisystem in 3, and of unknown etiology in 4 patients. The SMR for juvenile IIMs overall was 14.4 (95% confidence interval [95% CI] 12.2–16.5) and was 8.3 (95% CI 6.4–10.3) for juvenile DM. The top mortality risk factors in the univariable analysis included clinical subgroup (juvenile CTM, juvenile PM), antisynthetase autoantibodies, older age at diagnosis, ILD, and Raynaud's phenomenon at diagnosis. In multivariable analyses, clinical subgroup, illness severity at onset, age at diagnosis, weight loss, and delay to diagnosis were the most important predictors from RSF; clinical subgroup and illness severity at onset were confirmed by multivariable Cox regression analysis. Conclusion Overall mortality was higher in juvenile IIM patients, and several early illness features were identified as risk factors. Clinical subgroup, antisynthetase autoantibodies, older age at diagnosis, and ILD are also recognized as mortality risk factors in adult myositis.